Implementation of Napkin AI Technology in Cooperative Learning and Its Effect on Students' PAI Learning Outcomes - Mujahidah Mujahidah (AR-RASYID : Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the effect of applying a cooperative learning model assisted by Napkin AI media on the learning outcomes of fifth-grade Islamic Religious Education students at SDN 08 Watampone. Using a quantitative experimental approach, this study involved 25 fifth-grade students in the 2025/2026 academic year as subjects. Data were collected through multiple-choice learning outcome tests in the form of pretests and posttests, then analyzed using the Paired Sample t-Test. The results of the study showed a significant increase, where the average student score before treatment was 50.96, which is considered low, rising to 81.80 after treatment and categorized as high. The statistical test results with a significance value of 0.000 0.05 also confirmed the presence of a significant influence. The implementation of a cooperative learning model assisted by Napkin AI has been proven effective in improving students' PAI learning outcomes, as indicated by the change from a low to a high category and the significant influence between before and after the implementation.